Study and detection of relativistic Solar Neutrons at ground level with the Spherical Proportional Counter - Kyratzis, D.; Savvidis, I. (HNPS Advances in Nuclear Physics, 2019)
A novel method of high energy solar neutron detection is proposed with the Spherical Proportional Counter (SPC), taking advantage of the 209Bi(n,f) reaction. This reaction, is considered as a standard for high energy neutron detection, due to large cross section values in the 100 MeV – 1 GeV energy interval, obtained in the n_TOF facility at CERN. A thin spherical shell of Bismuth will be situated in the large volume of the SPC, serving as target for high energy neutrons bombarding the detector, thus resulting in fission fragment emission. Detailed simulation of the 209Bi(n,f) reaction with the INCL++ model, coupled with the ABLA07 de–excitation code is performed (cross section, mass & atomic number distribution, kinetic energy per fragment) in the 100 MeV – 10 GeV energy interval, together with SRIM for the fragments’ projected range in 209Bi. Experimental data from a 252Cf source are obtained, in order to validate the SPC’s efficiency in fission fragment detection. Calculations for the expected reactions in the 209Bi shell have been performed in different atmospheric depths (700 & 1000 g/cm2), and various spherical detector radii.